Detection and Monitoring of Surface Subsidence Associated with Mining Activities in the Witbank Coalfields Using Differential Radar Interferometry - Gift Makusha (International Conference on Ground Control in Mining, 2011)
Surface subsidence associated with coal mining activities in the Mpumalanga Province of South Africa changes the natural environment in several ways, and current challenges for mining companies include rehabilitation of the natural environment and the prevention of further degradation. To monitor the spatial and temporal evolution of surface subsidence, traditional fieldbased monitoring approaches such as GPS and spirit leveling are employed at a number of locations. However, the resulting measurements are point-based, and frequent revisitations are necessary to map the evolution of surface subsidence basins over time. To address these limitations, differential interferograms derived from repeat-pass satellite-borne synthetic aperture radar (SAR) systems were tested for their ability to measure and monitor surface deformation. The SAR data was captured by the European ERS-1 and ERS-2 satellite and covered a timeframe between 2008- 09-15 and 2008-09-15. The resulting interferograms revealed several features indicative of surface subsidence. Ground truth data confirmed the presence of a subsidence basin, detected using differential interferometry techniques during the 35-day period between April 12, 2008 and May 17, 2008; a maximum vertical deformation of 3.2 cm (1.3 in) was recorded. Interferometric monitoring revealed an eastward migration of the subsidence basin between June 2, 2008 and September 15, 2008 with an additional 4.7 cm (1.9 in) of subsidence observed. This migration coincides with the advance of the working face of the mine during this period. Finite element modeling will be performed in order to model the rates and evolution of surface subsidence haloes as underground mining advances. These presented results demonstrate the ability of interferometric synthetic aperture radar techniques to measure surface subsidence as well as the monitoring of the evolution of subsidence basins over time. This implies that the technique could be included, together with traditional field-based surveying techniques, in an operational monitoring system. With knowledge on deformation rates and subsidence basin evolution, informed decisions on current and future infrastructure development can be made and remedial actions and prevention strategies can be formulated for the problems associated with environmental degradation.